ألاصلاحات الهيكلية في الإقتصادات النامية. محاولة في المراجعة والتقييم (المجلة العراقية للعلوم الاقتصادية, 2018)
Economic reforms are necessary but not sufficient. Whats more important is the essence of reforms that must combine economic reforms with institutional and political. Most of the developing countries are still far-reaching from this implication. this is what I have tried to discuss in this research that can help to explain why developing countries failed to achieve the intended targets. The reform policy should focus on adapting the lessons from international experience and creating feasible and appropriate reforms for their own circumstances.